Amberlite-IR 120 catalyzed three-component synthesis of alpha-amino phosphonates in one-pot - Bhattacharya, Asish K.; Rana, Kalpeshkumar C. (Tetrahedron Letters, 2008)
A simple, efficient, and environmentally benign method for a three-component reaction of an amine, an aldehyde or a ketone, and diethyl phosphite catalyzed by Amberlite-IR 120 resin has been developed to afford alpha-amino phosphonates in high yields and short reaction times under solvent-free reaction conditions. The major advantages of the present method are good yields, inexpensive, ecofriendly and reusable catalyst, mild and solvent-free reaction conditions and tolerance towards various functionalities present in the substrates. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; alkyl phosphite; alpha-amino phosphonates; amines; ion-exchange resin; multi-component reaction

Antimycobacterial agent, (E)-phytol and lauric amide from the plant Lagascea mollis - Bhattacharya, Asish K.; Rana, Kalpeshkumar C. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2013)
Chemical examination of aerial parts of the plant, Lagascea mollis has resulted in the isolation of two compounds, an acyclic diterpene alcohol which has been identified as (E)-phytol 1 and lauric amide 3. Their structures have been elucidated by spectral data and chemical transformations. This is the first report of isolation of both these compounds from this plant It is noteworthy that compound 1 has been found to be a potent antimycobacterial agent and thus, L. mollis could be exploited as an alternative source.
Keywords: amide; chemical transformation; diterpene; Lagascea mollis; structure elucidation